Primary five pupils' computational estimation skills and related mathematical abilities - Siew, Kong Wai. (2009)
This study sought to investigate the relationships between problem-solving ability, mental-calculation ability and computational-estimation ability of primary 5 pupils. It also attempted to examine the strategies used by good student-estimators in solving computational-estimation problems.